The Implementation of Teaching and Learning English for Tourism of Tourism and Hospitality Majors - Suaidi, Muhammad; Pius, Ogoina Hembafan; Mengo, Nyabisi (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: This research aims to identify the English language learning strategies for tourism, the materials used in teaching English, and the difficulties students face in learning English at the Banjarmasin National Tourism Academy.Methodology: This descriptive qualitative research, designed by Miles and Huberman, involved first, third, and fifth-semester students, as well as an English lecturer of the Speaking course at the National Tourism Academy Banjarmasin. Data were collected through observation, interviews, and document analysis, and analyzed in three steps: data condensation (selecting and summarizing relevant documents), data display (organizing and compressing data), and drawing and verifying conclusions.Main Findings: The results showed that the teaching strategies for the Speaking course in tourism at the National Tourism Academy Banjarmasin primarily involved lecturing and discussion, with less emphasis on role play. The Speaking course is a basic course aimed at boosting students’ confidence in speaking English. The materials used in the course are general English topics such as obligatory expressions, hobbies and interests, and nominal sentences, which are not specifically related to tourism. Additionally, students reported difficulties in constructing sentences based on grammar rules and experienced burnout from online learning.Novelty/Originality of this study: This research provides new insights into effective methods for teaching and learning English in tourism and hospitality majors, highlighting strategies that enhance students’ practical English skills in the context of the global tourism industry.